General anaesthetics and the acetylcholine-sensitivity of cortical neurons. - Smaje, J C (1976)
1The effects of general anaesthetics on neuronal responses to iontophoretically-applied acetylcholine have been examined in slices of guinea-pig olfactory cortex maintained in vitro. 2 Acetylcholine excited 61% of the prepiriform neurones tested. The excitation was blocked by atropine, but not by dihydro-beta-erythroidine or gallamine. 3 Alphaxalone reversibly depressed the acetylcholine-sensitivity of prepiriform neurones. Pentobarbitone did not consistently depress the acetylcholine sensitivity of these cells. 4 Ether, methoxyflurane, trichloroethylene and halothane caused a dose-related augmentation of acetylcholine-induced firing. 5 These results show that general anaesthetics do not necessarily depress the sensitivity of nerve cells to all excitatory substances and that different anaesthetics may affect a particular excitatory process in various ways.